Sistem Pakar Diagnosa Penyakit Diabetes Pada Puskesmas Sandar Angin Kota Pagaralam Berbasis Web - Idi Jangcik (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2017)
The purpose of this study to solve specific problems, in this case, is to build a knowledge-based system of experts and doctors in diagnosing diabetes. Based on the preliminary study results through observation and interviews at the Puskesmas Sandar Pagar Alam Community Center, the facilities there have not been too far using the technology to identify diabetes where a patient should control the doctor directly without knowing the signs or causes of diabetes. From here the researcher will create the expert system by using web-based forward chaining reasoning by using PHP programming with MySQL database which quoted from diabetes expert and supporting book based on the result from preliminary study through observation and interview at Sandar Angin Pagaralam Community Health Center. By using rules based on questions that lead to diabetes to produce a decision of the question that passed. So as to produce a system that can be used to overcome all problems faced by patients for early diagnosis of diabetes and to help health professionals in delivering information about diabetes to patients.